Diagnosis and treatment of abnormal left coronary artery originating from the pulmonary artery: A single-center experience - Kahraman Yakut; Niyazi Kursad Tokel; Murat Ozkan; Birgul Varan; Ilkay Erdogan; Mehmet Sait Aslamaci (Anatolian Journal of Cardiology)
Objective: We aimed to review symptoms, findings, surgical treatment options, short- and mid-term outcomes, and reoperation rate of patients diagnosed with of left coronary artery from the pulmonary artery (ALCAPA) of an anomalous origin in our institution. Methods: From May 2000 to March 2018, 33 patients who had left coronary artery originating from the pulmonary artery were retrospectively examined. The clinical features of patients, diagnostic tools and their efficacy, outcomes of surgical repair, and problems during follow-up were evaluated. Results: Thirty-three patients (22 females, 11 males) were included in the study. At the time of surgery, the median age and weight of patients were 6 months (minimum/maximum, 1–166 months) and 6.5 kg (minimum/maximum, 3–38.5 kg), respectively. The mean follow-up was 5+-3.5 years (range, 1–16 years). Dyspnea, tachypnea, diaphoresis, prolonged feeding time, and developmental delay were common presenting signs and symptoms. It was determined that all the patients who were diagnosed at another center reached our center for surgical treatment within 1 month. Twenty-three (69.7%) patients had pathologic Q wave with anterior and/or anterolateral myocardial infarction signs on an electrocardiogram (ECG), whereas 22 (66.6%) patients had ST-T segment changes. Twenty-one (63.6%) patients had cardiomegaly on the telecardiogram. A reimplantation surgery was performed to 22 patients and 10 patients underwent the Takeuchi procedure. In addition to ALCAPA repair, 5 patients needed mitral valve plasty. Atrial septal defect (ASD) and ventricular septal defect (VSD) were closed in one patient, and Tetralogy of Fallot was totally corrected in another. At discharge, there was a significant improvement in left ventricular (LV) systolic functions. At the last visit, all patients had normal LV systolic functions except four who had mild dysfunction. The mean follow-up of the four patients was 2.8 years. In the early postoperative period, complications were seen in 10 patients. Five patients died in the early postoperative period, while one patient died 9 months after the ALCAPA surgery because of low cardiac output syndrome that developed after mitral repair. Conclusion: Patients with ALCAPA commonly present with congestive heart failure symptoms. When the diagnosis is confirmed in these patients, surgical treatment should not be delayed. The availability of surgical center and surgery outcomes for ALCAPA diagnosed patients are comparable with other countries, but the delay in the diagnosis of disease is still a problem in our country.